PELATIHAN MEDIA PEMBELAJARAN WORDWALL BAGI GURU-GURU SMP NEGERI 2 PAKIS - Anam, Ainul; Ashiddiqi, Hasbi; Khakim, Muhammad Lukmanul; Suhariyati, Suhariyati; Solikhin, Mukhammad (Jurnal Graha Pengabdian, 2023)
The purpose of this service activity is to help Pakis 2 Public Middle School teachers understand the use of WordWall learning media and provide innovative learning models that can attract students to learn through learning games. This activity was carried out by the Student Guidance Team at the State University of Malang which consisted of 3 people and was accompanied by a Mathematics lecturer and Mathematics teacher at SMP Negeri 2 Pakis. The method used in the implementation of community service uses lecture, discussion, and practice methods. Before and after the activity takes place, the teacher is given a pre-test, post-test, and questionnaire. The pre-test results obtained from this activity were 7% of the teachers already understood WordWall learning media. While the post-test gain from this activity was 93.5% which indicated that the teacher had understood the use of the WordWall learning media that had been provided. From the results of the questionnaire that has been given, it appears that there is a need for retraining with a different topic. This is because the learning media provided is very useful to assist teachers in carrying out interesting learning for students.